Biology, morphology and taxonomy of a snail-feeding leech from North Carolina, USA, provisionally identified as Helobdella lineata (Verrill, 1874) (Glossiphoniidae): First evidence for extra-oral digestion in the Hirudinea - Sawyer, Roy T. (Zootaxa, 2024)
This is a twelve-year longitudinal study of a common snail-feeding leech indigenous to the Albemarle region of northeastern North Carolina, USA. Based on contents of this paper the species is provisionally identified as Helobdella lineata (Verrill, 1874). For all practical purposes this is the first comprehensive description of this species. Particular attention is focused on variability of its dorsal papillae and variable pigment patterns within the Albemarle population. A total of 404 specimens were collected from 25 collecting stations in disparate parts of the region. Specialised leech traps set in these swamps were monitored regularly yielding unprecedented information on its morphology, ecology and general biology. This study recognises four principal pigment variants within the Albemarle region which, based on dissections, appear to represent a single biological species. Moreover, limited observations suggest that pigment variability is attributable primarily to adaptive camouflage to local surroundings. Methodologically it is emphasized in this paper that variable traits cannot serve as key taxonomic anchors. A proposed alternative diagnosis for identifying H. lineata is based entirely on more rigorous, non-variable characters. A significant finding is that H. lineata is most meaningfully understood in terms of specialist adaptation to feeding on snails. Furthermore, it is proposed that such adaptation required a major evolutionary shift within the foregut of this species. Evidence is presented that H. lineata uses uniquely large salivary cells to dissolves solid snail tissue into a semi-fluid state before ingestion via a specialised proboscis. This is the first example of extra-oral digestion in the Hirudinea.